ARS DEDICATORIA ÎN COLECŢIA BIBLIOTECII „TÂRGU-MUREȘ” - ȘATRAVCA, director, Filiala „Târgu-Mureș”, Claudia (BIBLIOPOLIS, 2020)
The article is about the book donations that increase the library collection. Dedications and autographs, belonging to men of culture or science, leaders, professional gives a sentimental value to the book, contribuite to establish friendship and partnership relations. The author, director of the Târgu-Mureș Branch, describe this special collection of the branch.